The Relationship Between Parity, History Of Antenatal Care (ANC), Pregnancy Complications, Estimated Fetal Weight and Fetal Presentation To The Selection Of Cesarean Section Action - Helmy Aries Stiawan; Aladin Aladin; Husna Yetti (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: There is an increase in caesarean sections trend globally. Caesarean section is generally performed to assist deliveries that cannot be carried out normally, but this also has a significant impact on both maternal and child health, as well as the economic burden so it is necessary to evaluate the factors that influence decision for caesarean section, to determine the relationship between parity, antenatal care Method: This study is an analytical observational study with a case control design conducted in July 2024 using medical record data of pregnant women who underwent caesarean section or vaginal delivery at the Pariaman City Regional General Hospital in the urban area and Sungai Dareh Regional Hospital at Dharmasraya in rural areas. The sample for this study were pregnant women who chose caesarean section and women after vaginal delivery who met the inclusion and exclusion criteria Results: In this study there were 354 pregnant women who underwent CS (n=177) and vaginal delivery (n=177). Bivariate analysis showed a relationship between parity (OR: 1.64 [95% CI: 1.07-2.52]; p=0.023), history of ANC (OR: 1.64 [95% CI: 1.06-2, 55]; p=0.026), pregnancy complications (OR:3.16 [95% CI: 1.98-5.03]; p=0.000), fetal presentation (OR: 2.02 [95% CI: 1.26-3.24]; p=0.003) and estimated fetal weight (OR: 1.98 [95% CI: 1.19-3.30]; p= 0.008) with the decision making of caesarean section. Multivariate analysis showed that the most influencing factors on the decision making of  caesarean section were pregnancy complications (OR 4.35 [95% CI: 2.58 – 7.34]; p= 0.000), fetal presentation (OR 3.21 [95% CI : 1.85 – 5.55]; p=0.000) and parity (OR 1.59 [95% CI: 1.01 – 2.52]; p=0.044). Conclusion: The factors that most influence the decision making of  caesarean section are pregnancy complications, fetal presentation, and parity.